2020
DOI: 10.21203/rs.3.rs-25724/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of retinal and choroidal variations in thyroid-associated ophthalmopathy using optical coherence tomography angiography

Abstract: Background: To investigate the difference in retinal nerve fiber layer (RNFL) thickness, choroidal thickness (CT) and superficial retinal vessels between thyroid-associated ophthalmopathy (TAO) patients and healthy controls. To identify the potential influencing factors for these parameters and evaluate their diagnostic abilities in TAO.Methods: 20 active TAO patients, 33 inactive TAO patients and 29 healthy participants were enrolled. TAO patients were divided according to the clinical activity score (CAS). R… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Dave et al 10 found an increased RNFL thickness in active TED eyes compared to inactive eyes and healthy eyes. Yu et al, 11 on the other hand, reported that active TAO patients had thinner RNFL thickness than inactive and healthy subjects. Casini et al 12 reported that the RNFL thickness was comparable among Graves’ orbitopathy(GO) patients, Graves’ Disease(GD) patients without GO and healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dave et al 10 found an increased RNFL thickness in active TED eyes compared to inactive eyes and healthy eyes. Yu et al, 11 on the other hand, reported that active TAO patients had thinner RNFL thickness than inactive and healthy subjects. Casini et al 12 reported that the RNFL thickness was comparable among Graves’ orbitopathy(GO) patients, Graves’ Disease(GD) patients without GO and healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…For the DON patients in the sight-threatening group, the edema of the optic disc could cause pRNFL thickening. The results of the thinning, thickening and no significant change of pRNFL in TAO patients in the literature [8][9][10][11][12] may be related to different grouping methods and different pathogenesis, in addition to ethnic differences. Casini et al 12 and Guo J, et al 14 reported that Ganglion cell layer (GCL) was thinned in the TAO group, and Yufei Wu et al 15 reported that GCC was thinned in the DON group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on TAO macular blood flows using OCTA showed that superficial vessel density was lower in active TAO [13], while the superficial vessel density in inactive TAO varied in different studies. Yu [14]and Cetin [15] found a significantly higher retinal vascular density in inactive TAO, while Frazil [16] and Dave [17] found retinal vessel density values were similar in inactive TAO to healthy subjects. Moreover, Natasha [18] observed a decrease in macular VD in inactive TAO patients.…”
Section: Discussionmentioning
confidence: 99%